An eight-coordinate ytterbium complex with a hexagonal bipyramid geometry exhibiting field-induced single-ion magnet behaviour. Issue 17 (8th April 2019) - Zhao, Wen; Cui, Huihui; Chen, Xiao-Yun; Yi, Gangji; Chen, Lei; Yuan, Aihua; Luo, Cheng-Lin
Abstract : An eight-coordinate Yb III (NO3 )3 ( t Bu3 PO)2 complex with ideal D 3h symmetry represent the first report of Yb III -SIM based on a hexagonal bipyramidal geometry. Abstract : Two isostructural eight-coordinate complexes Ln(NO3 )3 ( t Bu3 PO)2 (Ln = Yb, 1-Yb ; Tb, 2-Tb ) were synthesized and structurally analyzed by single-crystal X-ray crystallography. Both complexes feature a nearly perfect hexagonal bipyramidal LnO8 geometry with ideal D 3h symmetry. Magnetic measurements show field-induced slow magnetic relaxation for1-Yb, thereby presenting the first report of Yb III -based SIMs with a hexagonal bipyramidal coordinate geometry. In contrast, 2-Tb shows no significant out-of-phase ( χ ′′M ) ac signals.